Peran Notaris Dalam Pengesahan Dokumen Asing Pasca Diratifikasinya Konvensi Apostille - Brahmi, Made Santrupti; Suyatna, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 02 (2023)DO - 10.24843/AC.2023.v08.i02.p3, 2023)
The purpose of this research is to find out the role of a notary in his authority to carry out legalization after the ratification of the Apostille Convention. This study uses normative legal research related to the absence of norms regarding the role of notaries in legalizing private documents after the ratification of the Apostille Convention. This study uses statutory and conceptual approaches to analyze the authority and role of a notary in legalizing foreign documents after the ratification of the Apostille Convention. The results of this study can be concluded that the notary has the authority to legalize private documents or documents that will be used abroad as an initial step before legalization is carried out. After the ratification of the Apostille Convention, the role of a notary is increasingly needed not only as a public official authorized to carry out legalization but also as a general officer who is given the task and obligation to provide legal counseling to appearers, especially regarding the contents of the document and the validity of the document in the destination country.